Arf1 GTPase Regulates Golgi‐Dependent G2/M Transition and Spindle Organization in Oocyte Meiosis - Kun‐Huan Zhang; Yuan‐Jing Zou; Meng‐Meng Shan; Zhen‐Nan Pan; Jia‐Qian Ju; Jing‐Cai Liu; Yi‐Ming Ji; Shao‐Chen Sun (Advanced Science, 2024)
Abstract ADP‐ribosylation factor 1 (Arf1) is a small GTPase belonging to the Arf family. As a molecular switch, Arf1 is found to regulate retrograde and intra‐Golgi transport, plasma membrane signaling, and organelle function during mitosis. This study aimed to explore the noncanonical roles of Arf1 in cell cycle regulation and cytoskeleton dynamics in meiosis with a mouse oocyte model. Arf1 accumulated in microtubules during oocyte meiosis, and the depletion of Arf1 led to the failure of polar body extrusion. Unlike mitosis, it finds that Arf1 affected Myt1 activity for cyclin B1/CDK1‐based G2/M transition, which disturbed oocyte meiotic resumption. Besides, Arf1 modulated GM130 for the dynamic changes in the Golgi apparatus and Rab35‐based vesicle transport during meiosis. Moreover, Arf1 is associated with Ran GTPase for TPX2 expression, further regulating the Aurora A–polo‐like kinase 1 pathway for meiotic spindle assembly and microtubule stability in oocytes. Further, exogenous Arf1 mRNA supplementation can significantly rescue these defects. In conclusion, results reported the noncanonical functions of Arf1 in G2/M transition and meiotic spindle organization in mouse oocytes.